2023
DOI: 10.1101/2023.10.10.561753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secretory Leukocyte Protease Inhibitor Protects Against Severe Urinary Tract Infection in Mice

Anne L. Rosen,
Michael A. Lint,
Dayne H. Voelker
et al.

Abstract: Millions suffer from urinary tract infections (UTIs) worldwide every year with women accounting for the majority of cases. Uropathogenic Escherichia coli (UPEC) causes most of these primary infections and leads to 25% becoming recurrent or chronic. To repel invading pathogens, the urinary tract mounts a vigorous innate immune response that includes the secretion of antimicrobial peptides (AMPs), rapid recruitment of phagocytes and exfoliation of superficial umbrella cells. Here, we investigate secretory leukoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…In the control group, the majority of the top 20 DEGs were associated with the epithelial cells, including epithelial barrier‐related genes (CLDN4, KRT19, and KRT18), and SLPI, a key gene reported to be localized to bladder epithelial cells and protect against urinary tract infection in mouse model. 15 Also, the GO enrichment analysis confirmed that the functions of such DEGs were related to the epithelial function (Figure 2B ). As for the BOO group, interestingly, the top two DEGs, SCGB3A1 and SCGB1A1, which belong to the secretoglobin family, have been reported to play a crucial role in immune regulation and could potentially serve as biomarkers for lung tissue damage caused by mechanical ventilation.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In the control group, the majority of the top 20 DEGs were associated with the epithelial cells, including epithelial barrier‐related genes (CLDN4, KRT19, and KRT18), and SLPI, a key gene reported to be localized to bladder epithelial cells and protect against urinary tract infection in mouse model. 15 Also, the GO enrichment analysis confirmed that the functions of such DEGs were related to the epithelial function (Figure 2B ). As for the BOO group, interestingly, the top two DEGs, SCGB3A1 and SCGB1A1, which belong to the secretoglobin family, have been reported to play a crucial role in immune regulation and could potentially serve as biomarkers for lung tissue damage caused by mechanical ventilation.…”
Section: Resultsmentioning
confidence: 57%
“…In the control group, the majority of the top 20 DEGs were associated with the epithelial cells, including epithelial barrier-related genes (CLDN4, KRT19, and KRT18), and SLPI, a key gene reported to be localized to bladder epithelial cells and protect against urinary tract infection in mouse model. 15 Also, the GO enrichment analysis confirmed that the functions of such DEGs were related to the epithelial function (Figure 2B). As for the BOO tissue.…”
Section: Cell Type-specific Gene Expression and Function Profiles In ...mentioning
confidence: 57%